Speed and safety of mass spectrometry for identification of Burkholderia pseudomallei directly from spiked blood cultures. Issue 4 (22nd April 2022) - Gassiep, Ian; Bauer, Michelle J.; Harris, Patrick N. A.; Norton, Robert
Abstract : Burkholderia pseudomallei is a bipolar Gram-negative bacillus and the causative agent of melioidosis; an infectious disease which commonly presents with bacteraemia. Data regarding direct from blood culture identification of B. pseudomallei using the Vitek mass spectrometer (MS) are limited. The authors aim to assess the safety and sensitivity of the Vitek MS for identification of B. pseudomallei from spiked positive blood culture samples. Safety was assessed by determining the ability of the standard MS α-cyano-4-hydroxycinnamic acid (CHCA) matrix solution to inactivate B. pseudomallei . Organism identification using the manufacturer's blood culture extraction method was compared to an in-house technique. Additionally, identification following abbreviated agar incubation of blood culture broth was performed. All 70 MS target spots were inactivated by the matrix solution. The manufacturer's blood culture extraction method identified 0/26 (0%) B. pseudomallei samples. An in-house method using the spun deposit from blood culture broth samples identified 38/38 (100%) B. pseudomallei samples. MS analysis of a blood culture broth drop on Chocolate agar following a 6 h incubation identified 30/32 (94%) samples. Decreased time to diagnosis of melioidosis bacteraemia is likely to improve patient outcomes. This study adds to the literature with regards to the utility of MALDI-TOF MS identification of B. pseudomallei both directly from positive blood culture broth and a subsequent 6 h plate incubation. The use of a standard matrix solution inactivates the organism, and use of the spun deposit from a positive blood culture broth is most effective for early identification of B. pseudomallei .